PENGEMBANGAN BAHAN AJAR MATA KULIAH PEMBELAJARAN IPS SD MODEL 4-P DIPADUKAN DENGAN RECIPROCAL TEACHING - Mikael Nardi (JIPD (Jurnal Inovasi Pendidikan Dasar), 2017)
This study aims at producing teaching materials of lesson social study at primary school. This study used design into three phases: (1) preliminary study, (2) the development of the model, and (3) testing model. The research populations are fourth semester students of Teacher of Primary School Education departemen on STKIP St. Paul Ruteng in academic year 2013/2014. The research samples are two class (IIE and IIF). In the preliminary studies, the data were obtained from interview and observation, while at the stage of development model, the data were obtained from validation, questionnaire, and observation.At the stage of test model, the data were gathered from the test and analyzed by T test with a confidence interval of 95%.The results show that the teaching material model 4P integrated with reciprocal teaching is effective in increasing learning achievement.This was proved by the average result of post-test is higher for the students who were treated by the model 4P integrated with reciprocal teaching (exprimen class) than those not using that model (control class). Beside that, had positif respons of students on the teaching materials model 4P integrated with reciprocal teacing.